Implementasi Metode Simpleks Dalam Penentuan Keuntungan Pada Usaha Rumah Jahit Yulia - Simatupang, Leni Darsima; Febriani, Sindi; Nisa, Tarbiyatun; Wati, Yulia Prestia; Ritonga, Irmayanti (Universitas Labuhanbatu, 2025)
This research aims to apply the simplex method using QM for Windows software to determine the optimal benefits of the Yulia Sewing House. In the textile industry, efficient resource management is very important to increase profitability. Yulia Sewing House is faced with the challenge of utilising limited resources such as raw materials and labour to maximise profits from various products offered. The simplex method is used to solve linear program problems with the function of profit goals that want to be maximised and constraints such as production capacity or availability of raw materials. The data used in this research includes information on production costs, selling prices, and production capacity of each type of product. QM for Windows analyses to determine the optimal production mix. This research will make a significant contribution to strategic decision making in the management of Yulia Sewing House and can be a reference for other small and medium businesses to optimise the production process and increase the profitability of Yulia Sewing House. From the results thatObtained, the simplex method can be used to maximise. The profit with an increase in profit of Rp 2,800,000.